Strategi PT. Harum Jaya Dalam Mengembangkan Usaha Di Kabupaten Wakatobi Menerut Ekonomi Syariah - Sri alfianti; Aslan, La Ode; Gurudin, Siti Rahma (OIKONOMIKA : Jurnal Kajian Ekonomi dan Keuangan Syariah, 2025)
This study aims to explore the business development strategies implemented by PT. Harum Jaya in Wakatobi Regency from a sharia economic perspective. The research adopts a descriptive qualitative approach using field research methods. Data were collected through observation, in-depth interviews with the business owner, employees, and customers, as well as documentation review. The findings indicate that PT. Harum Jaya’s business development strategy is carried out through adaptive internal management, affordable pricing, service diversification, and a strong emphasis on service quality and customer proximity. The marketing strategy primarily relies on personal relationships, business reputation, and initial utilization of digital media. All business practices are implemented in accordance with sharia economic principles, such as honesty, justice, transparency, and the avoidance of usury (riba). In addition, social responsibility is reflected in the empowerment of local labor and the provision of affordable prices for students and the surrounding community. These findings suggest that the integration of business strategies and sharia economic values plays an important role in maintaining business sustainability within a local context.